Alternatives for the chemical control of sourgrass at post-emergence - Danilussi, Maikon Tiago Yamada; Lorenzetti, Juliano Bortoluzzi; Albrecht, Alfredo Junior Paiola; Barroso, Arthur Arrobas Martins; Albrecht, Leandro Paiola; Santos, Guilherme Rossano dos; Silva, André Felipe Moreira; Caneppele, Giuzeppe Augusto Maran (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the effectiveness of herbicides when applied alone and in combinations at sourgrass (Digitaria insularis) post-emergence, as well as to identify a substitute to paraquat in sequential application. Field and greenhouse experiments were conducted during the 2019/2020 and 2020/2021 crop seasons. The herbicides applied alone and in combinations were: atrazine, clethodim, clodinafop, diquat, glufosinate, haloxyfop, imazapic, imazapyr, mesotrione, nicosulfuron, paraquat, glyphosate, saflufenacil, tembotrione, and tepraloxydim. In the 2019/2020 crop season, in the experiment conducted in the field, the control of sourgrass was considered low due to the dry weather condition and to the full flowering of the plants. In the greenhouse, a satisfactory control above 80% was observed at 28 days after herbicide application for most treatments. In the 2020/2021 crop season, under field conditions, the application of glyphosate combined with haloxyfop, with a sequential application of glufosinate, resulted in the highest weed control. In the greenhouse, most treatments were effective and, of these, all contained glufosinate. The sequential application of glufosinate or in combinations favors a better control of sourgrass. However, diquat and glufosinate do not differ in efficacy in sequential application and are an option for the control of the weed.